Comprehensive Review on Amorphous Oxide Semiconductor Thin Film Transistor - Lee, Sang Yeol (Transactions on electrical and electronic materials, 2020)
Oxide materials are one of the most advanced key technology in the thin film transistors (TFTs) for the high-end of device applications. Amorphous oxide semiconductors (AOSs) have leading technique for flat panel display, active matrix organic light emitting display, active matrix liquid crystal display as well as thin film electronic devices due to their excellent electrical characteristics, such as field effect mobility ( μ FE ), subthreshold swing ( SS ) and threshold voltage ( V th ). Researchers from various fields have studied and considered ways to improve µ FE of AOS TFT, which has been studied for 16 years since 2004. Since 2004, mobility has been increased by using various methods, such as designing novel amorphous oxide materials, changing device structures, or adopting new post-treatment. The development of field effect mobility as well as the stability enhancement has been comprehensively reviewed in this report.